Analysis of Factors Affecting Rubber Production in Koto Alam Village, Pangkalan Koto Baru District, Lima Puluh Kota Regency, West Sumatra Province - Helentina Situmorang; Ermi Tety (Jurnal Penelitian Pendidikan IPA, 2026)
People's rubber plantations play an important role in the welfare of farmers, the country and the world. However, people's rubber production is still low and many rubber plants are unproductive. This study aims to analyze the factors that influence rubber production in Nagari Koto Alam, Pangkalan Koto Baru District, Lima Puluh Kota Regency. This research was conducted conducted from March 2020 to July 2020. The research method used multiple linear regression and purposive sampling. The results of the study showed test regression R square = 0.827 was obtained, meaning that 82.7 % of the variables of land area, labor, and number of rubber trees were able to explain rubber production.  Land area had 1.791 coefficient, a positive and significant effect. So, rubber farmers must expanded their land area Farmers. The number of rubber trees had a negative (0.099) and significant effect. Because did not maintain rubber trees properly, and many rubber plants was damaged. Labor had a negative (2.086) and insignificant effect on rubber production. So it is necessary to increase the maintenance and rejuvenation of rubber plants.